Bond and part strength in fused deposition modeling. Issue 2 (20th March 2017) - Coogan, Timothy J.; Kazmer, David Owen
Abstract : Purpose: The purpose of this paper is to investigate the factors governing bond strength in fused deposition modeling (FDM) compared to strength in the fiber direction. Design/methodology/approach: Acrylonitrile butadiene styrene (ABS) boxes with the thickness of a single fiber were made at different platform and nozzle temperatures, print speeds, fiber widths and layer heights to produce multiple specimens for measuring the strength. Findings: Specimens produced with the fibers oriented in the tensile direction had 95 per cent of the strength of the constitutive filament. Bond strengths ranged from 40 to 85 per cent of the filament strength dependent on the FDM processing conditions. Diffusion, wetting and intimate contact all separately affect bond strength. Practical implications: This study provides processing recommendations for producing the strongest FDM parts. The needs for higher nozzle temperatures and more robust feed motors are described; these recommendations can be useful for companies producing FDM products as well as companies designing FDM printers. Originality/value: This is the first study that discusses wetting and intimate contact separately in FDM, and the results suggest that a fundamental, non-empirical model for predicting FDM bond strength can be developed based on healing models. Additionally, the role of equilibration time at the start of extrusion as well as a motor torque limitation while trying to print at high speeds are described.